KEDUDUKAN KEPALA NEGARA DALAM SISTEM PEMERINTAHAN ISLAM (Analisis Kritis terhadap Peran Khalifah dalam Dustûr al-Islâmy Hizbut Tahrir) - Robitul Firdaus (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2019)
State leaders as leaders of government organizations have a strategic position in a state system. Hizbut Tahrir in the Draft Islamic Law (Dustûr al-Islâmy) which was first compiled by Taqiyuddin An-Nabhani even discoursed on great power in the hands of the head of state. A caliph (head of state) is not only dominant in the executive sector, but also has an important role in the legislative and judicial sectors as in the trias politica theory. This paper aims to critically analyze the role of the caliph in the Islamic government system as discoursed by Hizbut Tahrir. This is important because the regulation of the world of politics and the state cannot be solely based on the historical facts of Islamic civilization and ignores the development of the needs of the times and sociological factors. The rules regarding the caliphate contained in Dustûr al-Islâmi Hizbut Tahrir are still strongly influenced by the history of Islamic civilization at the time of the Prophet and Khulafâ' al-Rasyidn. The granting of enormous power to a khalfah is based on the assumption that the personal qualities of a caliph are on par with the Prophet and his chosen Companions. Of course this is not appropriate to be applied in today's era. Therefore, the power of the head of state must be limited and balanced. In this context, the offer of a modern democratic system through the mechanism of separation and division of power can be an offer to modify the Hizbut Tahrir caliphate system to achieve the ideal goal of 'Islamic government'.